Comparing selected parameters of a two-dimensional turbulent free jet on the basis of experimental results, digital simulations, and theoretical analyses - Skotnicka-Siepsiak, Aldona (Technical Sciences, 2016)
The presented experimental and digital examinations of a two-dimensional turbulent free jet are a first phase of in the study of the Coandă effect and its hysteresis. Additionally, basing on theoretical analyses, selected results for a turbulent jest have been also mentioned, considering theoretical assumptions for the wall layer. As the result, on the basis of experimental, digital, and analytical methods, a review of characteristic jet properties has been prepared, which includes a jet spreading ratio, its cross and longitudinal sections, and turbulence level. The jet spreading radio has been expressed as a non-linear function of the x : b relative length.